Frontispiece: Isovalent AgIII/AgIII, AgII/AgII, Mixed‐Valent AgII/AgIII, and Corrolato‐Based Mixed‐Valency in β, β′‐Linked [Biscorrolato‐silver]n Complexes. Issue 56 (9th October 2017) - Patra, Bratati; Sobottka, Sebastian; Sinha, Woormileela; Sarkar, Biprajit; Kar, Sanjib
Abstract : The power of the combination of electrochemistry, UV/Vis/NIR/EPR spectroelectrochemistry and DFT calculations for mapping the electronic structures of unusual disilver and dicorrole containing mixed‐valent compounds united in a surprisingly flexible structure is depicted in the artwork. The joining of the two corrole units to achieve this feat and the importance of the physical and theoretical methods are put into the larger context of the world. For more information see the Communication by B. Sarkar, S. Kar et al. onpage 13858 ff.